2013
DOI: 10.1002/term.1632
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human endometrial stem cells into urothelial cells on a three-dimensional nanofibrous silk-collagen scaffold: an autologous cell resource for reconstruction of the urinary bladder wall

Abstract: Reconstruction of the bladder wall via in vitro differentiated stem cells on an appropriate scaffold could be used in such conditions as cancer and neurogenic urinary bladder. This study aimed to examine the potential of human endometrial stem cells (EnSCs) to form urinary bladder epithelial cells (urothelium) on nanofibrous silk-collagen scaffolds, for construction of the urinary bladder wall. After passage 4, EnSCs were induced by keratinocyte growth factor (KGF) and epidermal growth factor (EGF) and seeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Endometrial stem cells are in fact a group of stem cells (adult stem cell), which are extracted from endometrial tissue of the uterus, which present some features similar to mesenchymal stem cells. Rehabilitation of the endometrial layer of the uterus in each menstrual cycle is due to these cells (17,30). Currently, mesenchymal stem cells are used in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial stem cells are in fact a group of stem cells (adult stem cell), which are extracted from endometrial tissue of the uterus, which present some features similar to mesenchymal stem cells. Rehabilitation of the endometrial layer of the uterus in each menstrual cycle is due to these cells (17,30). Currently, mesenchymal stem cells are used in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Poly L-lactide-co-glycolic (PLGA) is one of the synthetic polymers that has been used in clinics due to its good biocompatibility, controllable degradability and relatively good process ability (15,16). It was shown that, bioactive glass increase cohesion, development and osteogenic differentiation of stem cells (17,18). Combining polymers and bioactive glass, in order to obtain new composites, is a novel strategy in bone TE and the composites benefits, including enhancement of mechanical indices, enable better adhesion with bone tissue and bioactivity that progress new bone formation (19)(20)(21).…”
mentioning
confidence: 99%
“…Previously, mesenchymal stem cells derived from bone marrow and endothelial progenitors were used as a source of smooth muscle cells and vasculature in efforts to regenerate bladder in vivo [78,79]. Recently, a report of the derivation of urinary-epithelial cells from HEDSC suggested that the human endometrium may be an alternative autologous cell source for bladder regeneration [80]. In this study, CD146 + , CD105 + , CD90 + , and CD44 + HEDSC cells were isolated and plated on collagen-V, silk, and silk-collagen nanofibers, which provided a suitable 3D scaffold for HEDSC proliferation and tissue engineering applications.…”
Section: Differentiation To Urothelial Cellsmentioning
confidence: 98%
“…Apart from the common mesodermal lineages, endometrial MSCs may be induced to differentiate in vitro into skeletal and cardiac muscle, 86,87 insulin-producing cells 88 and the urinary epithelium 89 in the endodermic lineages and finally into neuronal cells [similar to neurolemmocytes, Schwann cells], 90,91 and dopaminergic neurons 91 in the ectodermic lineages. 28,92,93 Therefore, these cells might be used to treat affections such as cardiac disease, muscle degeneration, diabetes type 1 and neurodegenerative diseases in the future.…”
Section: Endometrium As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…89 Review articles 3,6-tetrahidropiridina (MPTP) neurotoxin has been demonstrated to produce cells with neuronal morphology in vivo that also express tyrosine hydroxylase (TH). Thus, this procedure increases the TH-positive cell numbers to form dopamine metabolite concentrations within the in vivo transplant site.…”
Section: Endometrium As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%